Young People as Agents of Change: The Mekong School’s Approach to Strengthening Young People’s Potential for Sustainable Development in the Mekong Subregion - Supitcha Punya (Journal of Mekong Societies, 2022)
The Mekong School was established in 2015 by the Institute of Traditional Knowledge, Chiang Khong Conservation Movement (or Rak Chiang Khong) as a community-based learning center to provide knowledge about Chiang Khong district and the Mekong River to local people, particularly young people. This article analyzes the approaches and challenges of the Mekong School in its support of young people in contributing to sustainable development in Chiang Khong district and the Mekong River area. The qualitative method was used to obtain data through interviews with the key participants from the Mekong School, a public school, as well as other young people. The research results show that the Mekong School currently has three approaches: 1) experience-based learning; 2) a joint curriculum with a public school; and 3) the Mekong youth forum, as a long-term plan. However, the Mekong School has faced many challenges, including time limitations, the Thai centralized education policy, the way in which young people conceptualize sustainable development, and young people’s capacities.